Learning from experience. - Schank, John F. (John Frederic), 1946-; LaCroix, F. W.; Murphy, Robert E.; Ip, Cesse; Arena, Mark V.; Lee, Gordon T., 1953- (RAND, 2011)
Large, complex submarine design and construction programs demand personnel with unique skills and capabilities supplemented with practical experiences in their areas of expertise. Recognizing the importance of past experiences for successful program management, the United Kingdom's Ministry of Defence (MOD) asked the RAND Corporation to develop a set of lessons learned from its Astute submarine program that could help inform future program managers. RAND reviewed the history of UK nuclear submarines, investigated how operational requirements were set for the Astute class; explored the acquisition, contracting, design, and build processes that the Astute program employed; and assessed the plans and activities surrounding integrated logistics support for the Astute. The impact of the substantial time gap between the design and build of the Astute and its predecessor nuclear submarines was greatly underestimated by the private sector and the MOD, and both parties underestimated the impact of the MOD's decision to shift responsibilities to the private sector. Designing and building a submarine requires careful management and oversight and a delegation of roles and responsibilities that recognizes which party--the shipbuilder or the government--is best positioned to manage risks.